New-Age-Diskurs in der polnischen Literaturwissenschaft, Literaturkritik und Lyrik der 70er und 80er Jahre Rekonstruktion eines Weltbildes - Miszewski, Brigitta (Slavistische Beitraege, 1995)
In the present work, an individualistic and mystical oriented flow of Polish literary criticism, literary criticism and poetry of the late 70s and 80s, characterized by the idea of ​​a "new privacy", a social and individual transformation, is investigated and used in a comprehensive context of the New Age discourse manifested in America and Europe since the late 1970s in various cultural areas.